Prognostic Value of the Platelet-to-Lymphocyte Ratio in Patients With Melanoma: A Meta-Analysis - Zhang, Feng; Gong, Weihong (Frontiers in Oncology, 2020)
Background: The prognostic role of the platelet-to-lymphocyte ratio (PLR) is controversial in patients with melanoma. Therefore, we performed a meta-analysis to assess the prognostic value of the PLR in patients with melanoma. Methods: PubMed, Web of Science, Embase, the Cochrane library, WanFang, and China National Knowledge Infrastructure were searched for eligible studies. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated to evaluate the association between the PLR and overall survival (OS) and progression-free survival (PFS). Results: Nine studies with 2396 patients were included in this meta-analysis. A high PLR was a predictor of shorter OS (HR=1.67, 95% CI=1.18–2.38, p=0.004), but not PFS (HR=1.53, 95% CI=0.96–2.44, p=0.075) in patients with melanoma. Subgroup analysis revealed that the PLR remained a significant prognostic indicator of both OS and PFS in patients with non-metastatic disease; the PLR cut-off value of <120 had a consistent prognostic value. Conclusions: An increased PLR was associated with poor OS of patients with melanoma. Hence, we suggest that the preoperative PLR could be used to identify high-risk patients and provide information regarding the prognosis of patients with melanoma.